Southeast Asia - Poole, Frederick King, 1934- (New York : Franklin Watts, 1968)
A brief description of the history, geography, people, culture and government of Southeast Asia in general, and specifically of each of its ten nations--Thailand, Burma, Malaysia, Singapore, North and South Vietnam, Cambodia, Laos, Indonesia, and the Philippines.
Keywords: Asia, Southeastern -- Juvenile literature